Metodologias ativas e a aprendizagem significativa: um quase-experimento com alunos da disciplina Análise de Custos - Rocha Neto, Isolfi Vieira (2020)
The accounting workforce has increasingly demanded skilled professionals to perform technical activities and to be able to learn and adapt to constant changes that occur in the accounting area. As a result, professors and academic managers of Higher Education Institutions offering Accounting courses are challenged to assess whether the teaching-learning process has enabled adequate training for students. Studies on accounting education have shown the contributions of active teaching methodologies to the teaching-learning process, from improvements in academic performance to the development of professional skills. Given this, the present study aimed to analyze whether the use of active methodologies in the discipline of Cost Analysis of the Accounting course contributes to significant learning of students enrolled in this discipline at the Federal University of Uberlândia, over the second academic semester of 2018. To do that, it used a mixed approach. The sample of this study is composed of 87 students, distributed in two groups: full-time shift and night shift. In the quantitative stage of this study, it used a quasi-experiment with a non-equivalent control group with replication of the experimental treatment. For this, two sample groups were formed (Experimental and Control Group) and the data treatment was conducted in two stages (First and Second Experimental Stage). Regarding the Experimental Groups, the active methods (Storytelling and Case method) were applied, while the traditional teaching methods (approaches based on expository methods) were used in the Control Groups. In the Second Experimental Stage, the application of the intervention between the groups is reversed so that the treatment started to be administered to that group that, previously, had not received it. Questionnaires were applied to identify students' socioeconomic profile, as well as Knowledge Tests to assess academic performance. The data obtained through the questionnaires were treated through descriptive analysis and tests of comparisons of means. After the Quasi-Experimental Steps were concluded, the Qualitative Step was carried out to examine the perspective of students on the use of active methodologies. In this phase, the intervention occurred in both classes by applying Fieldwork. The students' perception was collected through focus group interviews, carried out with students from both classes that make up this research sample. To interpret the statements from the interview, a Word Cloud was developed to analyze the content. The quantitative treatment of the results from the Knowledge Test revealed a statistically significant performance gain for students involved in active methodologies. In line with these results, the qualitative analysis made it possible to identify the following effects arising from the application of active methodologies: use of previous available knowledge; meaningful content, as well as connection with the reality experienced by students; willingness to learn how to learn; active posture in the development of activities; more time dedicated to studies; less tension during assessment; reinforced teacher-student bond; improvement of skills related to teamwork. It is concluded, therefore, that the necessary conditions for a significant learning (previous knowledge available; potentially significant content; willingness to learn), theorized by Ausubel (2000) and Ausubel, Novak and Hanesian (1980), were met when the active methodologies were used during the transmission of content in the Cost Analysis discipline.